Evaluating Financial Health in Indonesia's Infrastructure Sector: The Impact of Capital Structure, Liquidity, and Firm Size - Simanungkalit, Royhisar Martahan; Anugrah, Faisal; Jumono, Sapto; Adhikara, Muhammad Fachruddin Arrozi; Munandar, Agus; Suharna, Jaka (Golden Ratio of Finance Management, 2025)
This study analyzes the effect of capital structure, liquidity, and company size on financial performance. In this study, there are three independent variables, namely capital structure as measured by DER, liquidity as measured by Current Ratio, and company size as measured by total assets, and one dependent variable, namely financial performance as measured by ROA. The object of this research is infrastructure sector companies listed on the Indonesia Stock Exchange from 2021 to 2023 using secondary data, namely the companies' financial statements. The sampling technique in this study used a purposive sampling technique, with the number of samples obtained being 32 companies for 3 years, making a total of 96 sample data points. This study uses multiple linear regression analysis methods by conducting hypothesis testing to see its effect on financial performance. The results showed that the capital structure and liquidity variables negatively affected financial performance, while the company size variable did not affect the company's financial performance. This research can also be a consideration for companies to optimize capital structure management and increase company liquidity. The combination of debt and equity will be able to maximize profitability. Decisions regarding the use of debt must consider the risks that may arise as well as the potential return on investment. Thus, the company can improve its financial performance and provide positive signals to investors.